2011
DOI: 10.1016/j.jmbbm.2010.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Sub-10-micrometer toughening and crack tip toughness of dental enamel

Abstract: In previous studies, enamel showed indications to occlude small cracks in-vivo and exhibited R-curve behaviors for bigger cracks ex-vivo. This study quantifies the crack tip toughness (K I0, K III0 ), the crack closure stress and the cohesive zone size at the crack tip of enamel and investigates the toughening mechanisms near the crack tip down to the length scale of a single enamel crystallite. The crack-opening-displacement (COD) profile of cracks induced by Vickers indents on mature bovine enamel was studie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Besides measurements of stress-strain curves at different length scales, there have been contributions in enamel research investigating the submicrometre fracture toughness and toughening mechanisms with small-scale testing methods [25,26]. Apart from these, additional R-curve measurements provided greater insight into the orientation-related factors associated with crack growth resistance of enamel at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…Besides measurements of stress-strain curves at different length scales, there have been contributions in enamel research investigating the submicrometre fracture toughness and toughening mechanisms with small-scale testing methods [25,26]. Apart from these, additional R-curve measurements provided greater insight into the orientation-related factors associated with crack growth resistance of enamel at larger scales.…”
Section: Introductionmentioning
confidence: 99%
“…It has to survive millions of chewing cycles under complex-stress state conditions in the oral environment of the host even in the existence of severe internal cracks and flaws [17,18]. In order to meet this functional requirements enamel should possess damage tolerance capability as evidenced in the recent studies [19,20,21,22,23,24], which has been mainly attributed to the complex hierarchical and graded arrangement of its fiber-like mineral crystals and organic constituents.…”
Section: Dental Enamel Of Bovine Teethmentioning
confidence: 99%
“…More recently, R-curve measurements [20,22] revealed that the fracture resistance of enamel rises up to 4 MPa m 1/2 due to its graded structure and toughening mechanisms operating on all hierarchical levels [19].…”
Section: Dental Enamel Of Bovine Teethmentioning
confidence: 99%
See 2 more Smart Citations